UPAYA PENINGKATAN MOTIVASI BELAJAR MELALUI DIALOG KREATIF - Etin Solihatin (Jurnal Ilmiah Mimbar Demokrasi, 2012)
The operational objectives of this research is to increase the motivation to learn through creative dialogue. This study uses a class action (PTK) by the number of three cycles. The results showed that average scores on the motivation to learn or cycle 1 at 139.08 (77%). Average scores on the motivation of 141.46 or cycle (7.9%) and the average score of 147.26, or (82%). Thus the creative dialogue can enhance motivation to learn as much as 8%.